Pandangan Hukum Islam Tentang Status Hukum Bunga Bank (RIBA) - Suradi, Suradi; Mariana, Rani; Athoillah, Mohamad Anton (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze how Islamic law views the legal status of bank interest and problem solving provided by the Islamic economic legal system. In Islamic law, interest (riba) is a system and mechanism that is prohibited because it is contrary to the Qur'an and hadith. However, the system run by modern banking has not been recognized in Islam, so there are differences of opinion among Muslims. Using a normative approach, this article analyzes the sources of Islamic law on usury and looks for solutions offered in the Islamic economic system. The results of the study show that the rise of the Islamic economic legal system is based on the desire of Muslims to conduct Islamic economic transactions based on the teachings and doctrines of Islamic law. Keywords: Interest (Usury), Legal Status, Islamic Economics